2017
DOI: 10.1002/anie.201704054
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous endo and exo Complex Formation of Pyridine[4]arene Dimers with Neutral and Anionic Guests

Abstract: The formation of complexes between hexafluorophosphate (PF ) and tetraisobutyloctahydroxypyridine[4]arene has been thoroughly studied in the gas phase (ESI-QTOF-MS, IM-MS, DFT calculations), in the solid state (X-ray crystallography), and in chloroform solution ( H, F, and DOSY NMR spectroscopy). In all states of matter, simultaneous endo complexation of solvent molecules and exo complexation of a PF anion within a pyridine[4]arene dimer was observed. While similar ternary complexes are often observed in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…3b). 47 An X-ray structure of pyridine [4]arene crystals obtained from CHCl3 solution in the presence of n Bu4NPF6 showed that the amide tautomer predominates, with each pyridine [4]arene binding one PF6 − anion in an exo fashion by means of CHanion and ArH-anion interactions with the alkyl groups. Two pyridine [4]arenes then come together to sandwich CHCl3, which is bound in an endo mode.…”
Section: [H1] Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). 47 An X-ray structure of pyridine [4]arene crystals obtained from CHCl3 solution in the presence of n Bu4NPF6 showed that the amide tautomer predominates, with each pyridine [4]arene binding one PF6 − anion in an exo fashion by means of CHanion and ArH-anion interactions with the alkyl groups. Two pyridine [4]arenes then come together to sandwich CHCl3, which is bound in an endo mode.…”
Section: [H1] Instrumentationmentioning
confidence: 99%
“…First observed in the solid phase, such interactions evidently persist in the gas phase. Calculated from the CCS assuming a spherical conformation Obtained from molecular modelling.Table 1| A comparison of ionic diameters from IM, 1 H DOSY NMR, X-ray diffraction and molecular modelling 47,60,63. The collission cross-section (CCS) values were each obtained using an N2filled drift tube ion mobility (IM) spectrometer.Self-interlocked structures such as catenanes and [1]rotaxanes are special examples of host-guest systems.…”
mentioning
confidence: 99%
“…Despite their obvious structural similarities, pyridinearenes display different binding properties due to amide-iminol tautomerism and electronic properties arising from the pyridine ring. 6 From the two tautomeric forms, dihydroxy and hydroxy-oxo, only the latter has been observed in crystal structures. 6 Recently, conformational analysis for the tautomers also revealed that the hydroxy-oxo tautomer (Scheme 1) is ∼150 kJ mol −1 lower in energy than the dihydroxy tautomer.…”
Section: Introductionmentioning
confidence: 99%
“…6 From the two tautomeric forms, dihydroxy and hydroxy-oxo, only the latter has been observed in crystal structures. 6 Recently, conformational analysis for the tautomers also revealed that the hydroxy-oxo tautomer (Scheme 1) is ∼150 kJ mol −1 lower in energy than the dihydroxy tautomer. 7 The cavity of pyridinearene was earlier considered electron deficient and suitable to bind anionic guests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation